1 MEASUREMENT OF CLINIC HEART RATE AS A PREDICTOR OF MORTALITY IN PATIENTS WITH ASYMPTOMATIC STAGE II HYPERTENSION: A META-ANALYSIS. (July 2018) - Ciputra, Regina Nathania; Christanti, Mike; Dharma, I. Putu Pramana Sanitya
Abstract : Background: Heart rate (HR) is simple and inexpensive to measure in the clinical setting, and there is evidence to suggest that an increase in HR can potentially predict mortality in patients with asymptomatic severely elevated blood pressure, even in rates below 100 beats per minute (bpm). However, the prognostic value of HR in hypertensive patients has been both generally overlooked and inconsistent among studies. Objectives: To investigate the association between clinic resting HR and mortality in patients with asymptomatic stage II hypertension. Methods: We searched PubMed, Google Scholar, and MEDLINE for studies that evaluate the association between resting HR and all-cause mortality in patients with asymptomatic stage II hypertension. We used a random effects model to combine study-specific adjusted risk ratios and 95% confidence intervals (CIs). Results: A total of 11 prospective cohort studies with 59188 patients were included. Patients with resting HR of ≥80 bpm have a significantly higher risk (risk ratio, 1.36; 95% CI, 1.272, 1.454; p < .001) for all-cause mortality compared to patients with resting HR of <80 bpm. HR in patients with stage II hypertension is significantly associated with increased risk of all-cause mortality. Conclusion: Higher resting HR that is measured in the clinical setting is a significant predictor for all-cause mortality in patients with asymptomatic stage II hypertension, even in rates below 100 bpm. This indicates that resting HR provides simple and valuable prognostic information for patients presenting to the clinic with severely elevated blood pressure.